Terrorism, 2013-2015: a worldwide chronology - Mickolus, Edward F. (McFarland & Company, Inc., Publishers, 2016)
"This second comprehensive chronology of international terrorist attacks covers three years during which the Islamic State supplanted al Qaeda as the most active, well financed and well armed terrorist group. Domestic and international incidents are covered, outlining trends and exploding myths. The author examines the enigmas of contemporary terrorist behavior and offers indicators and predictions to watch for"--